Justice and reconciliation after the violence - Rigby, Andrew (Lynne Rienner Publishers, 2001)
How do societies that have been wracked by violent conflict reconcile themselves to their recent history? This book investigates differing approaches to "policing" the past, ranging from mass purges at one end of the spectrum to collective social amnesia at the other.